Genetic and hormonal control of vascular tissue proliferation. (February 2016) - Smet, Wouter; De Rybel, Bert
Graphical abstract: Highlights: Oriented cell divisions shape the vascular cell lineage throughout development. The genetic and hormonal pathways controlling vascular proliferation are slowly being interconnected, resulting in a detailed framework for vascular proliferation. A major challenge is to understand how these molecular factors control the actual orientation of cell divisions. Abstract : The plant vascular system develops from a handful of provascular initial cells in the early embryo into a whole range of different cell types in the mature plant. In order to account for such proliferation and to generate this kind of diversity, vascular tissue development relies on a large number of highly oriented cell divisions. Different hormonal and genetic pathways have been implicated in this process and several of these have been recently interconnected. Nevertheless, how such networks control the actual division plane orientation and how they interact with the generic cell cycle machinery to coordinate these divisions remains a major unanswered question.